A preliminary study on the diatom distribution of the main lakes in the city of Guiyang, Guizhou Province - Liu Yang; Yang Li; Zhao Chendi; Long Yunchun; Chen Jiaying; Chen Liang; Wu Jingjie; Hu Sunlin (E3S Web of Conferences)
Diatoms are a group of unicellular algae distributed throughout the world in a wide range of aquatic environments. Their unique biological and structural properties have propelled their applications in two critical fields: water environment monitoring and forensic science. In the presented paper, we surveyed the diatom distribution of the main lakes in the city of Guiyang, Guizhou Province, including diatom abundance, relative proportion of each genus, size distribution, which provided the necessary basis to improve water quality assessment frameworks and establish a foundational diatom dataset for forensic applications.